Birth out of Wedlock - Marietta Pongraćz (Hungarian Demographic Research Institute, 2002)
The crucial question here is whether the continuous increase of births out of wedlock expected throughout Europe and in Hungary will be accompanied by a change in the internal content of the relationship between the parents that will make this family form more stable. As increasing numbers choose this living arrangement, will this sort of family relationship become increasingly similar to the pattern of marriage-based family life, and the only difference will be official documentation of the partnership? Furthermore, are mothers raising their children alone rely only on themselves and truly on their own or do new alternatives of family life present an option for them? For example parents although living in separate homes continue to have strong emotional ties. By answering these questions we shall be able to develop novel approaches in terms of the legal, social and family policies for the problems related to births out of wedlock.The above questions were also incorporated into the survey conducted by the Demographic Research Institute in 1996. The survey sample consisted of 1,500 mothers that gave births out of wedlock in 1995. The primary goal of this survey was to identify how conscious the decisions of these mothers were to have a baby without having a legal relationship with a partner. This involved several questions concerning the nature of their decision to give birth out of wedlock. Was their choice determined by their value system? If so, was this a final decision or was it the result of necessity stemming from individual circumstances that do not exclude future marriage. These questions aimed at answering if an irreversible process was observable eroding the traditional form of family life based on marriage or if cohabitation would evolve as an alternative to legal marriage also surviving the changes. Furthermore the question how these processes will effect the situation, role and stability of families is also of great interest for us.
Keywords: 300; Nichteheliche Kinder; Ungarn